2017
DOI: 10.1080/21614083.2017.1400857
|View full text |Cite
|
Sign up to set email alerts
|

Learnings and challenges to deploy an interprofessional and independent medical education programme to a new audience

Abstract: The importance of interprofessional education (IPE) in continuing medical education and professional development has long been recognised by health organisations and academic societies, benefiting not only patient outcomes and interprofessional relationships but also overall health systems and workforce shortage. We report on the outcomes of an Australian IPE activity on medication-overuse headache (MOH) with general practitioners (GPs) and community pharmacists as learners. The design of the activity, which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Driel, et al highlighted the importance of interprofessional education in CME which has benefits for patients. 15 Curran et al (2010) described CME as professional support for rural physicians for their recruitment and retention. 16 CME is found to be supportive and encouraging for physicians working in remote and rural areas of Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Driel, et al highlighted the importance of interprofessional education in CME which has benefits for patients. 15 Curran et al (2010) described CME as professional support for rural physicians for their recruitment and retention. 16 CME is found to be supportive and encouraging for physicians working in remote and rural areas of Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' lack of awareness of medication overuse as a cause of headaches, reluctance to acknowledge how much medication they take, and poor adherence to recommended treatment have been identified as barriers to detection and management of MOH. A survey of Australian general practitioners (GPs) 19 showed that GPs' awareness of MOH is low, although the awareness of codeine overuse in general may have increased following the TGA's decision, which was widely discussed in the media. In Singapore, a general practice survey of patients and their attending physicians in a primary care setting found that 22.6% of the patient population reported taking acute pain medication for headaches at least 4 days per week.…”
Section: Problems With Detection and Treatment Of Medication Overuse mentioning
confidence: 99%